Computer aided software for low power transformer application / Muhammad Azmi Mohamed Dani - Mohamed Dani, Muhammad Azmi (1994)
The objective of this project is to develop a software to cater on the design of Low Power Transformer Le. Shell type and Core type of transformer. A C++ language Version 3.0 by Borland is used in creating the software. This software helps to determine die important parameters that are required in designing a low power transformer. The software wffl display such as the losses, efficiency, voltage regulation and the dimension of transformer.